1996
DOI: 10.1172/jci118551
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal rise of leptin in lean, obese, and non-insulin-dependent diabetes mellitus subjects.

Abstract: We studied 24-h profiles of circulating leptin levels using a sensitive and specific RIA in lean controls and obese subjects with or without non-insulin-dependent diabetes mellitus (NIDDM) during normal routine activity. Serum leptin levels were significantly higher in obese (41.7 Ϯ 9.0 ng/ml; n ϭ 11) and obese NIDDM (30.8 Ϯ 6.7; n ϭ 9) subjects compared with those in lean controls (12.0 Ϯ 4.4, n ϭ 6). In all the three groups, serum leptin levels were highest between midnight and early morning hours and lowest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

58
422
9
21

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 727 publications
(510 citation statements)
references
References 27 publications
58
422
9
21
Order By: Relevance
“…Thus, the CSF:plasma leptin ratio is lower in girls, and this may underlie the propensity towards excess body fat [33]. A nocturnal plasma leptin surge entrained to meal timing has been demonstrated in lean and obese humans [34,35]. However, this is not accompanied by an increase in CSF leptin [36].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the CSF:plasma leptin ratio is lower in girls, and this may underlie the propensity towards excess body fat [33]. A nocturnal plasma leptin surge entrained to meal timing has been demonstrated in lean and obese humans [34,35]. However, this is not accompanied by an increase in CSF leptin [36].…”
Section: Discussionmentioning
confidence: 99%
“…The plasma leptin level is known to vary somewhat throughout the day (46,47), and, apparently, the amplitude of the diurnal variations is influenced by factors, such as diet composition, physical activity, insulin levels, and energy balance (46,48,49). Therefore, fasting leptin concentration may not reflect the mean leptin concentration during the day.…”
Section: Discussionmentioning
confidence: 99%
“…The most likely reason for this was the lower pulse-to-noise ratio present at low leptin secretion rates (19). Sinha et al (27) have recently reported a nocturnal rise in serum leptin in lean and obese nondiabetic subjects, and in obese diabetic patients who ate three meals and one snack. These authors were unable to establish circadian rhythmicity because of the shortness of blood sampling.…”
Section: Discussionmentioning
confidence: 99%